11.1k views
4 votes
1). 10 = 4x +x

2). -6 = -2x -5 -1

3). -15 = 2v +v

4). -6 = 2v +4v

5). -2x +x = 5

6). -a -a = -8

7). -5p -6p = 0

8).-3k -6k = -9

9). 38 +7x = 5(1+8x)

10). -30 -8x = -6(x+5)

11).4(-4n+12)= 3(n-3)

12). 2(5+5x) = 8(x+1)

explain step by step plzzz

User Bparker
by
5.0k points

1 Answer

5 votes

Answer:

Explanation:

1). 10 = 4x +x 2). -6 = -2x -5 -1 3). -15 = 2v +v 4). -6 = 2v +4v 5). -2x +x = 5 6). -a-example-1
1). 10 = 4x +x 2). -6 = -2x -5 -1 3). -15 = 2v +v 4). -6 = 2v +4v 5). -2x +x = 5 6). -a-example-2
User Whme
by
4.8k points